Prevalence and risk factors for nephrolithiasis in adults with cystic fibrosis: A retrospective cohort study - Da Yeon Ryoo; Nolan Ladd; Stacey Culp; Spencer Harris; Gretchen Murray; Mariel McGuinness; Stephen E. Kirkby; Ganesh Shidham; Anne Rice; Kristen M. Roberts; Georgios I. Papachristou; Phil A. Hart; et al. (PLoS ONE, 2026)
Background Calcium oxalate nephrolithiasis is more common in persons living with cystic fibrosis (PwCF) than in the general population. A primary risk factor is exocrine pancreatic insufficiency (EPI) causing enteral hyperoxaluria. However, the relationship between nephrolithiasis and degree of EPI control has not been assessed. Methods A retrospective cohort study was conducted including all PwCF seen at our institution from 2018 to 2023 (n = 332). Collected data included socio-demographics, Charlson comorbidity index, EPI control status adjudicated by treating clinicians (classified as controlled, uncontrolled, or unknown), and nephrolithiasis events, which were classified as symptomatic or asymptomatic when nephrolithiasis were discovered incidentally on imaging. Incidence and lifetime prevalence rates were calculated for the entire sample and according to EPI control. A multivariable logistic regression model for the outcome of nephrolithiasis was performed using likelihood-ratio-based backwards stepwise selection. Results The cumulative lifetime prevalence of any nephrolithiasis event in our study population was 32%. The lifetime prevalence was higher in EPI (32%) than no EPI (24%), but there was no significant difference in prevalence according to EPI control status. The multivariable model identified that small bowel resection (odds ratio [OR] 3.0, 95% confidence interval (CI) 1.0–9.0)), alcohol use (OR 1.7, 95% CI 1.0–2.9), and decreased BMI (OR 0.9, 95% CI 0.9–1.0) were independently associated with nephrolithiasis. Among 105 individuals with nephrolithiasis, 51% (n = 54) had recurrent events. An invasive procedure was required by 10% (n = 3) with a single nephrolithiasis event and was required by 61% (n = 33) with recurrent nephrolithiasis. Conclusions Nephrolithiasis events are common in PwCF. We observed an increased prevalence among PwCF with EPI, but did not observe a difference based on the degree of EPI control although this may be limited by reliance on clinician assessment of EPI control rather than a more objective measure. Prospective investigation with detailed assessment of risk factors including dietary habits and EPI control is warranted.